CASH POSITION, DEBT TO EQUITY RATIO, RETURN ON ASSET DAN FIRM SIZE TERHADAP DIVIDENT PAYOUT RATIO - Setiawan, Edi; Zamzani, Faizal Ridwan; Amelia, Nur Fitri (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2018)
This research is aimed to knowing and analyzing the effect of the cash position, debt to equity ratio, return on asset and firm size to divident payout ratio. The type of data used in this study is pool data which is a combination time series, and cross section. panel data regression anlaysis test, election panel data reression estimation techniques, heteroscedasticity test, regression model analysis, and regression model testin and regression coefficients. The result showed that the partial debt to equity ratio and firm size no significantly influence the divident payout ratio, while the cash position, return on asset significantly influence the divident payout ratio. Simultaneously, cash position, debt to equity ratio, return on asset and firm size variable have a significant to divident payout ratio.